Individual-level discrimination in song characteristics of white-rumped shama, Copsychus malabaricus - Kumar Anil; Himanshu; Rawal Prakhar (Scientific Publishers, 2025)
Passerines exhibit considerable variations in song characteristics , with crucial ecological, behavioural and conservation implications. We documented the individual variations and level of distinctness in the song characteristics of white-rumped shama, Copsychus malabaricus. Bioacoustic analysis revealed that songs were composed of repeated strophes (2-5 types per individual) with occasional whistles/trills or orphan syllables, made up of 3-13 elements, with dissimilar structures. Data analysis using 373 strophes from 22 males showed that all 8 variables (minimum, maximum, dominant and range of frequency, strophe duration, song rate, number of elements per strophe and type of element per strophe) differed significantly (P < 0.001). Song variations were higher among individuals compared to within individuals. The principal component analysis explained 56.87% variance. Discriminant function analysis exhibited 69.41% cumulative variance with 40.37% classification accuracy. The present study may be useful for further research on some other attributes of a song such as repertoire size, microstructure and seasonal/diurnal variations.